Physical activity in asthma control and its immune modulatory effect in asthmatic preschoolers. Issue 4 (4th October 2021) - Maurer, Debbie J.; Liu, Chengyao; Xepapadaki, Paraskevi; Stanic, Barbara; Bachert, Claus; Finotto, Susetta; Gao, Ya‐Dong; Graser, Anna; Jartti, Tuomas; Kistler, Walter; Kowalski, Marek; Lukkarinen, Heikki; et al.
Abstract: Background: The impact of physical activity on immune response is a hot topic in exercise immunology, but studies involving asthmatic children are scarce. Our aims were to examine whether there were any differences in the level of physical activity and daily TV attendance, to assess its role on asthma control and immune responses to various immune stimulants. Methods: Weekly physical activity and daily television attendance were obtained from questionnaires at inclusion of the PreDicta study. PBMC cultures were stimulated with phytohemagglutinin (PHA), R848, poly I:C, and zymosan. A panel of cytokines was measured and quantified in cell culture supernatants using luminometric multiplex immunofluorescence beads‐based assay. Results: Asthmatic preschoolers showed significantly more TV attendance than their healthy peers (58.6% vs. 41.5% 1–3 h daily and only 25.7% vs. 47.2% ≤1 h daily) and poor asthma control was associated with less frequent physical activity (PA) (75% no or occasional activity in uncontrolled vs. 20% in controlled asthma; 25% ≥3 times weekly vs. 62%). Asthmatics with increased PA exhibited elevated cytokine levels in response to polyclonal stimulants, suggesting a readiness of circulating immune cells for type 1, 2, and 17 cytokine release compared to subjects with low PA and high TV attendance. This may also represent a proinflammatory state in high PA asthmatic children. Low physical activity and high TV attendance were associated with a decrease in proinflammatory cytokines. Proinflammatory cytokines were correlating with each other in in vitro immune responses of asthmatic children, but not healthy controls, this correlation was more pronounced in children with sedentary behavior. Conclusion: Asthmatic children show more sedentary behavior than healthy subjects, while poor asthma control is associated with a substantial decrease in physical activity. Our results suggest that asthmatic children may profit from regular exercise, as elevated cytokine levels in stimulated conditions indicate an immune system prepared for responding strongly in case of different types of infections. However, it has to be considered that a hyperinflammatory state in high PA may not be beneficial in asthmatic children. Abstract : Asthmatic children show more sedentary behavior than healthy peers, especially those with uncontrolled asthma. Regular moderate‐to‐high PA is associated with elevated cytokine levels in response to viral, bacterial, and fungal stimulations in asthmatics, which indicates a strong immune response and readiness to respond upon infections. High cytokine levels associated with high PA might also indicate hyperinflammation, suggesting the need for individual assessment to find an optimum PA level. Abbreviations: PA, physical activity; TVA, TV attendance